Effects and safety of triamcinolone acetonide-controlled common therapy in keloid treatment: a Bayesian network meta-analysis - Zhang Z; Cheng L; Wang R; Cen Y; Li Z (Dove Medical Press, 2018)
Zhenyu Zhang,1 Lihui Cheng,2 Ru Wang,1 Ying Cen,1 Zhengyong Li1 1Department of Aesthetic Plastic and Burn Surgery, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 2Department of Pancreatic Surgery, West China Hospital, Sichuan University, Chengdu, People’s Republic of China Background: Triamcinolone acetonide (TAC) is used frequently in the treatment of keloid scars, but has presented controversial results. In this study, we aim to evaluate the effectiveness of TAC compared with other common therapies used in keloid treatment. Methods: MEDLINE, Embase, Web of Science and the Cochrane Library databases were searched until January 2018. Key data were extracted from eligible randomized controlled trials. Both pairwise and network meta-analyses were conducted for synthesizing data from eligible studies. Results: Ten randomized controlled trials were included in this meta-analysis. The relative risk of keloids associated with seven adjuvants was analyzed, including placebo, pulsed dye laser (PDL), 5-fluorouracil (5-FU), silicone, verapamil, TAC+5-FU and TAC+5-FU+PDL. Patients treated with the following adjuvants appeared to not have significantly reduced risk of keloid in relation to those treated with TAC: placebo (OR=1.86, 95% CI 1.12–2.61), PDL (OR=1.32, 95% CI 0.53–3.30), 5-FU (OR=1.13, 95% CI 0.48–2.68), silicone (OR=1.28, 95% CI 0.59–2.78), verapamil (OR=1.86, 95% CI 0.67–5.14), TAC+5-FU (OR=0.77, 95% CI 0.38–1.58) and TAC+5-FU+PDL (OR=0.80, 95% CI 0.16–4.03). The surface under the cumulative ranking curve values for each adjuvant were as follows: TAC, 59.9%; placebo, 17.4%; PDL, 46.3%; 5-FU, 48.9%; silicone, 56.2%; verapamil, 84.7%; TAC+5-FU, 68.5% and TAC+5-FU+PDL, 18.1%. Conclusion: There were no differences between the efficacy of TAC and other common therapies in keloid treatment. TAC also acts as an effective alternative modality in the prevention and treatment of keloids. Incorporating adjuvants particularly verapamil appeared to be significantly associated with a decreased risk of keloids. Keywords: keloid, triamcinolone acetonide, randomized controlled trial, network meta-analysis